A Tale of Two Monasteries : Westminster and Saint-Denis in the Thirteenth Century - Jordan, William Chester, 1948- (Book collections on Project MUSE., 2009)
A Tale of Two Monasteries takes an unprecedented look at one of the great rivalries of the Middle Ages and offers it as a revealing lens through which to view the intertwined histories of medieval England and France. This is the first book to systematically compare Westminster Abbey and the abbey of Saint-Denis--two of the most important ecclesiastical institutions of the thirteenth century--and to do so through the lives and competing careers of the two men who ruled them, Richard de Ware of Westminster and Mathieu de Vendome of Saint-Denis. Esteemed historian William Jordan weaves a breathta.